POLITICAL PARTICIPATION OF CHURCH IN BOGOR IN ELECTION IN 2018 (STUDY OF CHURCH POLITICAL COMMUNICATION IN THE DEMOCRACY PROCESS IN BOGOR CITY) - Andreas Bramantyo (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
The Regional Head Election which held simultaneously in 2018 is a momentum of revival in the political of world. Catholics who are also part of Indonesian society must take part in it. Bogor Diocese is a particular church in relation to the Roman Catholic Church. Bogor is also one of the places where simultaneous regional elections are held. Therefore the Catholics in the Bogor Diocese region automatically participated in this regional election. However, there are concerns that arise from the Bogor Diocese on the apathy of the people in political participation due to a lack of understanding of the methods of political participation and the lack of information about politics. Departing from this problem, various information was explored in the study, both from the congregation and church leaders in the Bogor Diocese, and supplemented with literature on the political participation of the church in Bogor Diocese in the 2018 Regional Election. In exploring of this information, the theoretical foundation used to complete the research is democratic theory, groupthink theory, and dramaturgy theory. From the results of the research, it can be found that the church in the Bogor Diocese still invites people to be involved in political participation. The church must also call for and convey the information to the people in various ways. To convey the information, church leaders must have a political understanding so the people get an understanding that politics is not a taboo.